2016
DOI: 10.3945/ajcn.115.129783
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin, procyanidins, cocoa, and appetite: a randomized controlled trial,

Abstract: Our nonalkalized cocoa mixture was associated with an acute decrease in food intake only after being supplemented with epicatechin. It is possible that epicatechin at a dose of >1.6 mg/kg body weight, alone or in concert with appropriate catalytic cocoa compounds, may be useful for helping people control their food intakes. This trial was registered at clinicaltrials.gov as NCT02408289.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 21 publications
0
48
1
Order By: Relevance
“…In multiple studies that recorded the outcomes over several hours on just one or two days, respectively, participants were instructed to refrain from exercise 24 to 48 h before test day [28,51,60,61,62,65,75] and to arrive after an overnight fast at the test center [52,57,62,69,70,76,86]. The bioactive phytochemical was mostly taken with a standardized meal, varying from a breakfast meal with approximately 1150 kJ (275 kcal) [73] to a breakfast buffet with a total amount of approximately 32,962 kJ (7878 kcal) [61].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In multiple studies that recorded the outcomes over several hours on just one or two days, respectively, participants were instructed to refrain from exercise 24 to 48 h before test day [28,51,60,61,62,65,75] and to arrive after an overnight fast at the test center [52,57,62,69,70,76,86]. The bioactive phytochemical was mostly taken with a standardized meal, varying from a breakfast meal with approximately 1150 kJ (275 kcal) [73] to a breakfast buffet with a total amount of approximately 32,962 kJ (7878 kcal) [61].…”
Section: Resultsmentioning
confidence: 99%
“…Several methodological weaknesses were observed, including the inclusion of just one gender [15,28,49,50,57,60,67,71,75,76], single blinding [21,60,70], a high dropout rate (>20%) [21,28,55,58,62], a small group size (parallel-designed RCTs with just 20 participants) [68,87], and a short intervention period (parallel-designed RCTs less than 1 month) [68].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be acknowledged that while an 319 independent measure of overall polyphenol concentration was obtained for each kind of 320 chocolate used in the present study, it is unclear whether the observed effects were associated 321 with specific individual polyphenols, or the combined mixture. For instance, there is evidence 322 15 to suggest that epicatechin acutely reduces ad libitum energy intake in healthy, young 323 volunteers (32). Future research is needed to identify the role of specific polyphenols, as well 324 as their interactions when present in various combinations.…”
mentioning
confidence: 99%